Warehouse Data System Analysis PT. Kanaan Global Indonesia - Tino Feri Efendi; Mutiya Krisanty (Institut Teknologi Bisnis AAS Indonesia, 2020)
Data Warehouse is a computer system for archiving and analyzing historical data of an organization. An organization copies information from its operational systems to a warehouse. The purpose of this research is to help provide information in supporting the decision-making process in the field of sales, purchasing and material inventory control at PT Kanaan Global Indonesia. PT Kanaan Global Indonesia previously presented the data warehouse manually. By designing a data warehouse system, company leaders can be more assisted in making decisions that are faster and more precise. The research method used includes analysis of observations, interviews, documentation and literature study. The result of this research is the availability of a data warehouse that can produce fast and precise information, thus helping the company in making decisions.Keywords— Data, Information, Warehouse